The transformation of surveillance in the digitalisation discourse of the OECD: A brief genealogy - Michaela Padden (Internet Policy Review, 2023)
In democratic states, mass surveillance is typically associated with totalitarianism. Surveillance practices more limited in their scope draw criticism for their potential to undermine democratic rights and freedoms and the functioning of representative democracies. Despite this, citizens living in political systems classed as democratic are increasingly subject to surveillance practices by both businesses and governments. This paper presents the results of a genealogy of OECD digitalisation discourse from the 1970s to the present to show how both harms and benefits of surveillance practices have been problematised. It shows how practices once considered unacceptable are increasingly portrayed as neutral, or even positive. A shift is identified from general agreement over the incompatibility of surveillance practices with democracy to greater acceptance of those practices when rebranded as tools to promote customisation, economic growth or public health. This transformation is significant because it: (1) shows the inherent instability of policies anchored to seemingly fixed or self-evident concepts such as 'well-being' or 'public interest'; (2) highlights the fragility of democratic systems when things deemed harmful to their operation can be repurposed and subsequently permitted; and (3) highlights the contingency of (seemingly inevitable) surveillance practices, thereby opening up a space in which to challenge them.
Keywords: 300; Profiling; Surveillance; Digitalisation; Organisation for Economic Co- operation and Development (OECD); Democracy